Microphones on Unmute: Perceived Online English-Speaking Anxiety of Non-Native EFL Educators - Ayar, Zülal (International Review of Research in Open and Distributed Learning, 2026)
While teachers worldwide rapidly switched to emergency remote teaching almost overnight owing to the unprecedented global pandemic, the rise of artificial intelligence (AI) has further transformed language education paradigms. Although previous research has explored foreign language teaching anxiety (FLTA), the self-perceived online L2 speaking anxiety of teachers remains underexplored. Accordingly, this study has been designed on a wide scale to address this lacuna by focusing on the perceptions of anxiety of 179 non-native EFL teachers at the Ministry of Education and instructors in higher education contexts. Moreover, it aimed to reveal its provoking reasons and finally the reported reflections of educators’ apprehension on virtual classes. To that end, qualitative and quantitative data were gathered in a complementary fashion through semi-structured interviews and an online survey developed by the researcher. The study identified the lack of perceived competence, troubles with online technologies, and learners’ English proficiency as factors leading EFL educators to experience online L2 speaking anxiety despite their self-confidence. Their reported reflections also disclosed that self-confidence without competence would be of almost no use in language teaching. Finally, some significant differences were detected between the participants’ demographic variables and their online L2 speaking anxiety.